2016
DOI: 10.1097/md.0000000000005318
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus-related esophageal cancer survival

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…We observed that HPV status does not in uence patient's survival, although HPV positive individuals have a longer survival in relation to HPV negative individuals. These results are in line with previous reports on esophageal cancer, that shown that HPV infection is not associated with improved survival, suggesting that the presence of HPV may not be useful for a possible prognostic assessment related to fact or that contribute to cancer of the esophagus 58,59 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that HPV status does not in uence patient's survival, although HPV positive individuals have a longer survival in relation to HPV negative individuals. These results are in line with previous reports on esophageal cancer, that shown that HPV infection is not associated with improved survival, suggesting that the presence of HPV may not be useful for a possible prognostic assessment related to fact or that contribute to cancer of the esophagus 58,59 .…”
Section: Discussionsupporting
confidence: 92%
“…11, 70; 6 probably high risk: HPV-26, 53, 66, 68, 73, 82; and 11 high risk: HPV-16,18,31,33,35,39,45,52,56,58,59 …”
mentioning
confidence: 99%
“…Unlike the high prevalence of HPV in cancer of the cervix, the detection rate in ESCC is highly variable even within high-risk areas, averaging 19.8% in Africa and 27.7% worldwide. The major oncogenic strain, HPV16, has only been detected in 11.4% of ESCC cases (93,94). HPV viral genomes per cell are very low, if present at all, and the sequencing of viral-cellular DNA junctions has not been validated (93).…”
Section: Other Potentially Harmful Factorsmentioning
confidence: 99%
“…HPV viral genomes per cell are very low, if present at all, and the sequencing of viral-cellular DNA junctions has not been validated (93). Several other squamous cell cancers have a positive prognosis if found to be HPV-positive; however, this is not the case with ESCC (94,95). It is currently accepted by the majority, that a role for HPV, if any, remains elusive.…”
Section: Other Potentially Harmful Factorsmentioning
confidence: 99%
“…The prognostic value of HPV status has previously been investigated in patients with ESCC [ 19 21 ]. The first meta-analysis investigating overall survival in HPV-related esophageal cancer was published in 2016, and showed no significant association between HPV infection and survival [ 22 ]. The controversial results of the included studies are in contrast to oropharyngeal lesions, where HPV-positivity has been consistently shown to be a strong positive prognostic factor in patient outcomes [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%